Information Security And IT Governance Policies Application : A Study Of Prudential Malaysia - Halim, Elisa Mardiana (2009)
This paper is aimed to describe key information concerning IT governance and information security, such as, the characteristics of IT governance and information security , the guidelines, policies and tools used and the issues faced by organizations in realizing a 'healthy' level of its related controls.